Mixed-Valence Compounds as Polarizing Agents for Overhauser Dynamic Nuclear Polarization in Solids** - Gurinov, Andrei; Sieland, Benedikt; Kuzhelev, Andrey; Elgabarty, Hossam; Kühne, Thomas D.; Prisner, Thomas; Paradies, Jan; Baldus, Marc; Ivanov, Konstantin L.; Pylaeva, Svetlana (Angewandte Chemie International Edition, 2021)
Herein, we investigate a novel set of polarizing agents—mixed-valence compounds—by theoretical and experimental methods and demonstrate their performance in high-field dynamic nuclear polarization (DNP) NMR experiments in the solid state. Mixed-valence compounds constitute a group of molecules in which molecular mobility persists even in solids. Consequently, such polarizing agents can be used to perform Overhauser-DNP experiments in the solid state, with favorable conditions for dynamic nuclear polarization formation at ultra-high magnetic fields.
CRIS-Team Scopus Importer:2023-03-20
Keywords: ab initio calculations; DNP in solids; mixed valence compounds; molecular dynamics; Overhauser effect